Disturbances of ocular movements and blinking in schizophrenia. - Stevens, J R (1978)
Neurological examination and electroencephalograms and electro-oculograms, recorded by telemetry, from unmedicated patients with acute and chronic schizophrenia demonstrate a number of abnormalities of extraocular movement including staring, abnormal blink rate, absent glabellar reflex, and increase in horizontal eye movements. As potential clues to the pathophysiology of schizophrenia, these disturbances are analysed in relation to anatomical substrate and dopamine modulation of ocular movement, rapid eye movement sleep, and the neurological disorders in which similar disturbances of ocular movement occur.